The Latest Time Point of Retreatment (LTPR) as a Novel Method to Determine Antibacterial Effects for Binary Use of Cold Atmospheric Plasma and Conventional Agents - Schramm, Sandra; Hiller, Karl-Anton; Cantzler, Sylvia; Weilemann, Hannes; Cantzler, Maximilian; Zimmermann, Julia L.; Cieplik, Fabian; Maisch, Tim (Frontiers in Microbiology, 2020)
Multi-resistant microorganisms are a long-standing problem for public healthcare, as inactivating those resistant pathogens with conventional antibiotics or antiseptics often no longer achieves the expected clinical success. The aim of this in vitro study was to investigate the antibacterial efficacy of binary combinations of conventional antibacterial agents with cold atmospheric plasma (CAP), when both are applied in non-lethal concentrations. In this study, Enterococcus faecalis biofilms were treated with CAP in binary combinations with benzalkonium chloride (BAC), chlorhexidine (CHX) or ciprofloxacin (CIP), respectively, which were applied in different sequences. In order to evaluate effects of binary use of two different antibacterial approaches, the so-called latest time point of retreatment (LTPR) was defined. For this purpose, regrowth curves of the bacteria were measured following the respective treatment combinations. LTPR is defined as the time component of the inflection point of a normalized regrowth curve and allows the rating and interpretation of single or binary treatments with different agents or approaches. Furthermore, LTPR designates the latest time point where a retreatment appears to be appropriate for preventing regrowth of the bacteria in case the first treatment was not lethal. Here in our study, the binary combination of 10 min CAP with BAC, CHX or CIP leads to higher LTPRs as compared to single treatments for both sequences of application. Overall, the combination of two antimicrobial approaches is an effective alternative for inactivating bacteria in biofilms instead of a single treatment. Thus, LTPR provides a novel promising way to determine antibacterial effects for single or binary use of given antimicrobial approaches.